2014
DOI: 10.1289/ehp.1307562
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Polybrominated Diphenyl Ether Exposures and Neurodevelopment in U.S. Children through 5 Years of Age: The HOME Study

Abstract: Background: Polybrominated diphenyl ethers (PBDEs) are persistent chemicals that have been widely used as flame retardants in furniture, carpet padding, car seats, and other consumer products during the past three decades.Objective: We examined whether in utero exposure to PBDEs is associated with child cognitive function and behavior in a U.S. study sample.Methods: In a prospective birth cohort, we measured maternal serum concentrations of BDE-47 and other PBDE congeners in 309 women at 16 weeks of gestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(139 citation statements)
references
References 38 publications
9
128
0
2
Order By: Relevance
“…For example, Herbstman et al (2010) reported that prenatal BDE-47 levels were adversely associated with the 12-month (Bayley Scales of Infant Development-II) Psychomotor Development Index (PDI) (n¼ 118), 24-month Mental Development Index (MDI) (n¼ 117), and 48-month full-scale and verbal IQ (the Wechsler Preschool and Primary Scale of Intelligence, Revised Edition) (n¼ 104) in children from New York. In contrast, Chen et al (2014) reported that prenatal BDE-47 levels were not associated with PDI or MDI at ages 1-3 years (n ¼285 at 1 year, 239 at 2 years, 220 at 3 years) but negatively associated with Full-Scale IQ (the Wechsler Preschool and Primary Scale of Intelligence-III) and hyperactivity score (the Behavioral Assessment System for Children-2) at age 5 years (n ¼179) in children from Cincinnati. In a study of 62 Dutch children at age 5-6 years, Roze et al (2009) reported that prenatal PBDE (including BDEs 47, 99, 100, 153, and 154) levels were negatively associated with fine motor coordination and sustained attention, although such levels improved coordination and visual perception and led to fewer internalizing and externalizing behaviors.…”
Section: Introductionmentioning
confidence: 89%
“…For example, Herbstman et al (2010) reported that prenatal BDE-47 levels were adversely associated with the 12-month (Bayley Scales of Infant Development-II) Psychomotor Development Index (PDI) (n¼ 118), 24-month Mental Development Index (MDI) (n¼ 117), and 48-month full-scale and verbal IQ (the Wechsler Preschool and Primary Scale of Intelligence, Revised Edition) (n¼ 104) in children from New York. In contrast, Chen et al (2014) reported that prenatal BDE-47 levels were not associated with PDI or MDI at ages 1-3 years (n ¼285 at 1 year, 239 at 2 years, 220 at 3 years) but negatively associated with Full-Scale IQ (the Wechsler Preschool and Primary Scale of Intelligence-III) and hyperactivity score (the Behavioral Assessment System for Children-2) at age 5 years (n ¼179) in children from Cincinnati. In a study of 62 Dutch children at age 5-6 years, Roze et al (2009) reported that prenatal PBDE (including BDEs 47, 99, 100, 153, and 154) levels were negatively associated with fine motor coordination and sustained attention, although such levels improved coordination and visual perception and led to fewer internalizing and externalizing behaviors.…”
Section: Introductionmentioning
confidence: 89%
“…Yolton and coworkers found proportionately steeper decrements in reading abilities at the lowest levels of secondhand smoke exposure among US children, but this finding has not been replicated (137). For other established or emerging toxins, such as PCBs, organophosphate pesticides, and PBDEs, the lowest level at which adverse effects occur is less clear, but the linear relationship does not suggest a threshold (12,24,36,52,97,113,114). In contrast, some evidence supports a threshold for some mercury-induced deficits (108).…”
Section: Quantifying the Impact Of Toxins On Brain Developmentmentioning
confidence: 98%
“…For most toxins, there is insufficient evidence to draw any firm conclusions about specific windows of vulnerability. For example, exposure to PBDEs has been studied in five prospective birth cohort studies (24,36,46,52,106), but only two tested whether prenatal or postnatal PBDE exposure was more strongly associated with neurobehavioral end points (36,46). Eskenazi and her colleagues found that certain end points were more strongly associated with prenatal PBDE exposures, whereas other end points were more strongly associated with childhood exposures (36).…”
Section: Vulnerability Of the Developing Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental and Health and Safety (EHS) concerns associated with e-waste recycling exist [4,20,21,23,[25][26][27][28][29][30][31][32][33][34]. However, informational gaps are present.…”
Section: E-plasticsmentioning
confidence: 99%